Sufism of Morality According to Ibn Sina - Nelly Agustina; Siti Marisa; Amroeni Drajat; Salminawati Salminawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Research on the essence of Akhlaki Sufism is a study centered on the sanctification of morals, character, which tries to present good behavior (commendable) and stay away from bad traits (despicable). The approach of this study is the documentation study model and library study. Furthermore, Akhlaki Sufism is related to the two sides of the same coin, there is no Sufism without morality, and there is no morality without Sufism. In practice, morality can regulate horizontal relationships between human beings, while Sufism regulates vertical communication between humans and their Lord. Morals are the basis of the implementation of Sufism so that in practice Sufism is concerned with morals. The study of Islamic education with moral Sufism is to build human beings with noble character.